PENGARUH PENDIDIKAN KESEHATAN TENTANG INFEKSI SALURAN PERNAFASAN AKUT (ISPA) TERHADAP KEMAMPUAN IBU DALAM PERAWATAN ISPA PADA BALITA - Raisha Octavariny; Dwi Handayani (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Disease of bronchi represent one of the cause of death and painfulness at child especially at baby. Knowledge was result 'soybean cake', and this happened after people do to an certain object so that from the knowledge can influence mother action to treatment of disease of ISPA. This Research aim to to know influence of education of health about Acute Infection Channel Exhalation ( ISPA) to ability of mother in treatment of ISPA at Countryside of Sidodadi Ramunia District Wish. this Research type was eksperimental, desain research of experiment quasi (sham experiment) with device model of time design series. Population [at] this elite was all new mother have one child people and of sampel counted 21 people, technique of sampel totally sampling, data collecting method by holding an interview with indirectly by using sheet of kuesioner, data analysis by using test of Paired Sample t-test. Pursuant to result of analysis of that pValue ( 0,04) ( 0,05) which was hypothesis accepted by that was there was influence of education of health about Acute Infection Channel Exhalation (ISPA) to ability of mother in treatment of ISPA at balita. was for that expected to health energy so that can execute counselling of health as one of the health promotion action so that can prevent ISPA at child and can improve health of child.